Research and Application of Prognostics and Health Management Technology Framework in Heavy Haul Locomotive - ZHOU Zhansong (Kongzhi Yu Xinxi Jishu)
Focused on the problem of inefficient maintenance of heavy haul electric locomotives, the comprehensive technology of data acquisition and processing, fault diagnosis and warning, health assessment and maintenance decision-making adopted in current maintenance management and academic research in China are studied. A framework of prognostics and health management (PHM) is proposed in this paper to ensure the operational safety of heavy haul locomotives. This framework is consist of four key systems, including pantograph catenary, traction, braking and running system. This framework can realize the health and maintenance management of locomotives through online status monitoring, real-time state assessment and conditional maintenance decision support, and promote the maintenance mode upgrading of heavy haul locomotives from traditional planned preventive maintenance to condition based maintenance. It also provides a good theoretical basis and guidance for solving the contradiction between heavy haul locomotive operation safety and maintenance economy, and realizing locomotive condition based maintenance. At the same time, traction motor, the key equipment of traction system, is taken as a case to analyze and verify the proposed PHM technology based on the existing control signals. It effectively solves the problems of insufficient coverage of detection items and insufficient diagnostic ability of existing locomotive PHM system.